Goal-driven sensor configuration in a navigation system - Zhen Zhu; Adams, Kayland; Venable, Don; Campbell, Jacob (IEEE/ION Position Location and Navigation Symposium, 2016)
This paper presents a systematic approach to configure the sensor suite and measurement preprocessing functionality in a navigation system. The sensors and the user platform will be abstracted and represented with generic models. Various types of resources on the platform including processing capability, power consumption and payload capability are included in the platform model. Navigation performance will be optimized to meet the goals of specific missions, subject to the constraints on the onboard resources. A non-linear programming process is adopted to solve the constrained optimization problem.